The relationship between URG4 and clinicopathologic parameters and its effect on two-year survival in gastric carcinoma - Ethem Ömeroğlu (Translational Oncology, 2024)
Aim: Gastric cancer (GC) is the third leading cause of cancer-related deaths worldwide. The present study examined the relationship between Upregulated gene 4 (URG4) expression, an oncogene involved in the development of gastric carcinoma, and clinicopathologic parameters including Human epidermal growth factor receptor 2 (HER2) status. The study aimed to investigate the importance of URG4 as a prognostic factor for 2-year survival in GCs, which are usually in the advanced stage at the time of diagnosis and have a rapid course. Methods: In 61 patients with GC, URG4 expression results in paraffin blocks were compared with the patients' clinicopathologic, 2-year survival, and HER2 results. Results: Among the patients, 24 (39 %) had low URG4 scores (scores 0–4) and 37 (61 %) had high URG4 scores (scores 6–9). While the HER2 score was negative in 52 (85 %)patients, it was positive in 9 (15 %). URG4 expression values were significantly correlated with tumor (T) stage and lymphovascular invasion (LVI) (p < 0.005), whereas no significant correlation was determined between other pathological prognostic factors and HER2 status (p > 0.005). During the two-year period, 32 (52 %) patients survived and 29 (48 %) died. The mean duration of survival was 75.20 ± 35.22 weeks. A significant correlation was determined between URG4 values and survival and mortality results (p < 0.05). Conclusion: We revealed a correlation (p < 0.005) between increased URG4 scores with increased T stage and LVI. We demonstrated an association between increased URG4 expression and survival time and mortality in patients with GC during the first two years of survival (p < 0.005) and URG4 and HER2 yielded similar results as prognostic factors in the survival of the patients URG4 is an essential oncogene in malignancies, especially in gastric GC, requiring further research and development in prognostic and therapeutic areas.